2010
DOI: 10.1097/ogx.0b013e3181cb8fbc
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dengue and Pregnancy Outcomes

Abstract: After completion of this educational activity, the participant should be better able to assess symptoms of dengue fever and locations where dengue fever occurs, describe possible perinatal complications of maternal dengue fever, and identify the limitations of available literature describing dengue fever in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
98
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(104 citation statements)
references
References 24 publications
2
98
0
4
Order By: Relevance
“…This finding remained significant in a multivariable analysis adjusting for other well-established SD risk factors such as macrosomia and GDM. The recurrence rate found in our study is consistent with previously published retrospective studies [16][17][18][19]. In previous work evaluating SD incidences during the years 1988-2008, there was a steady decline in the incidence of SD [8].…”
Section: Discussionsupporting
confidence: 94%
“…This finding remained significant in a multivariable analysis adjusting for other well-established SD risk factors such as macrosomia and GDM. The recurrence rate found in our study is consistent with previously published retrospective studies [16][17][18][19]. In previous work evaluating SD incidences during the years 1988-2008, there was a steady decline in the incidence of SD [8].…”
Section: Discussionsupporting
confidence: 94%
“…Recurrence risks for shoulder dystocia have been quoted to range from approximately 10% to 25%. 10 We found that nearly 40% of Central Association of Obstetricians and Gynecologists members would allow a trial of labor in a patient with a documented history of a prior vaginal delivery complicated by shoulder dystocia. Possible explanations for this lack of consensus include the lack of randomized trials and insufficient data among patients with prior shoulder dystocia.…”
Section: Discussionmentioning
confidence: 98%
“…Pregnancy is a state of relative maternal immune suppression to accommodate the semi-allogeneic fetus [5,6,7]. The clinical features of CCHF infection are well known.…”
Section: Introductionmentioning
confidence: 99%